Impacts of Nutrients on Alkene Biodegradation Rates and Microbial Community Composition in Enriched Consortia from Natural Inocula - Emily Byrne; Simeon Schum; Laura Schaerer; Stephen M. Techtmann (Microbiology Spectrum, 2023)
ABSTRACT There is a growing need for biological and chemical methods for upcycling plastic waste streams. Pyrolysis processes can accelerate plastic depolymerization by breaking polyethylene into smaller alkene components which may be more biodegradable than the initial polymer. While the biodegradation of alkanes has been extensively studied, the role microorganisms play in alkene breakdown is not well understood. Alkene biodegradation holds the potential to contribute to the coupling of chemical and biological processing of polyethylene plastics. In addition, nutrient levels are known to impact rates of hydrocarbon degradation. Model alkenes were used (C6, C10, C16, and C20) to follow the breakdown capability of microbial communities from three environmental inocula in three nutrient levels over the course of 5 days. Higher-nutrient cultures were anticipated to exhibit enhanced biodegradation capabilities. Alkene mineralization was assessed by measuring CO2 production in the culture headspace using GC-FID (gas chromatography-flame ionization detection), and alkene breakdown was directly quantified by measuring extracted residual hydrocarbons using gas chromatography-mass spectrometry (GC/MS). Here, the efficacy of enriched consortia derived from the microbial communities of three inoculum sources (farm compost, Caspian Sea sediment, and an iron-rich sediment) at alkene breakdown was investigated over the course of 5 days across three nutrient treatments. No significant differences in CO2 production across nutrient levels or inoculum types were found. A high extent of biodegradation was observed in all sample types, with most samples achieving 60% to 95% biodegradation of all quantified compounds. Here, our findings indicate that alkene biodegradation is a common metabolic process in diverse environments and that nutrient levels common to culture media can support the growth of alkene-biodegrading consortia, primarily from the families Xanthamonadaceae, Nocardiaceae, and Beijerinkiaceae. IMPORTANCE Excess plastic waste poses a major environmental problem. Microorganisms can metabolize many of the breakdown products (alkenes) of plastics. While microbial degradation of plastics is typically slow, coupling chemical and biological processing of plastics has the potential to lead to novel methods for the upcycling of plastic wastes. Here, we explored how microbial consortia derived from diverse environments metabolize alkenes, which are produced by the pyrolysis of polyolefin plastics such as HDPE, and PP. We found that microbial consortia from diverse environments can rapidly metabolize alkenes of different chain lengths. We also explored how nutrients affect the rates of alkene breakdown and the microbial diversity of the consortia. Here, the findings indicate that alkene biodegradation is a common metabolism in diverse environments (farm compost, Caspian sediment, and iron-rich sediment) and that nutrient levels common to culture medium can support growth of alkene-biodegrading consortia, primarily from families Xanthamonadaceae, Nocardiaceae, and Beijerinkiaceae.